Combined Biopsy and Imaging-Guided Microwave Ablation by Using a Coaxial Guiding Needle. Issue 1 (7th May 2021) - Wu, Yi-Wei; Chan, Gabriel; Huang, Ivan Kuang Hsin; Kwan, Justin; Lim, Gavin Hock Tai; Quek, Lawrence Han Hwee; Pua, Uei
This article demonstrates the technique of using a coaxial guiding needle to perform combined percutaneous biopsy and microwave ablation via a single tract. From May 2019 to July 2020, 14 patients underwent combined biopsy and microwave ablation by using a coaxial guiding cannula. Tumors were in the kidney of six patients (43%), the liver of six patients (43%), and the lung in two patients (14%). The diagnostic yield of biopsy was 86% (12/14). Ablation technical success rate was 100%. In conclusion, using a coaxial guiding needle in microwave ablation and biopsy is safe and effective.